Pengembangan dan Evaluasi Nebulizer Portable untuk Pengiriman Obat Respirasi yang Efisien di Rumah menggunakan Arduino Nano - Hidayat, Ahmad Hilman; Rahmadewi, Reni (Jurnal Ilmiah Wahana Pendidikan, 2024)
Air pollution is a condition where one or more physical, chemical, or biological substances are present in the air, reaching hazardous levels for humans, animals, and plants. In Indonesia, more than 70% of air pollution originates from motor vehicle emissions. Motor vehicles produce exhaust gases that accumulate in the air. Among the hazardous chemicals that emerge are lead (Pb), photochemical oxidants (Ox), nitrogen oxides (NOx), hydrocarbons (HC), carbon monoxide (CO), and many others. One of the primary direct impacts of air pollution is on human respiratory health, causing various complaints such as lung diseases and upper respiratory tract infections. Meanwhile, the latest data from WHO indicates that the number of deaths due to air pollution has increased to 7 million people per year. This is because more than 90% of people on Earth inhale air with a high level of pollutants. To reduce the mortality rate due to respiratory disorders, regular treatments are needed, one of which is Nebulization Inhalation Therapy. Nebulization inhalation therapy involves the administration of inhalation medication using a nebulizer. This therapy method is effective and efficient in delivering medication in aerosol form directly to the respiratory and lung tract quickly and relatively safely compared to systemic therapy. The types of drugs commonly administered with a nebulizer include bronchodilators, mucolytics, and anti-inflammatories